Empowering Children With Special Needs (ABK) Through Character Education Based On Local Wisdom In Bali - ANGGRENI, PUTRI (Universitas Nahdlatul Ulama Surabaya, 2025)
Law No. 20 of 2013 concerning the national education system, article 3, requires character building from an early age. Hindu religious education is a subsystem of national education. In addition to encouraging spiritual intelligence, education also strives to produce students who are intellectually and emotionally intelligent. In its implementation, education for children with special needs at SLB Negeri 3 Denpasar is based on the values of Balinese local wisdom. If students can understand, internalise, and apply these values, it is certain that their personalities in both school and non-school settings will prioritise positive aspects rooted in Balinese local wisdom, such as Tri Hita Karana, Tat Twam Asi, and Mayama Braya. Therefore, the implementation of education for children with special needs (ABK) based on these local wisdom values of Bali in schools must be further prioritised to cultivate a generation of young people who are of high quality and noble character.